2017
DOI: 10.1037/pas0000304
|View full text |Cite
|
Sign up to set email alerts
|

The Inventory of Psychotic-Like Anomalous Self-Experiences (IPASE): Development and validation.

Abstract: Anomalous self-experiences (ASEs) are among the first symptoms to appear in the prodrome, predict the development of psychosis over and above clinical symptoms, and are common in people with schizophrenia. Although there are well-validated phenomenological interviews for assessing ASEs, there are no self-report measures. The current research describes 4 studies designed to develop and validate a new scale to assess ASEs: the Inventory of Psychotic-Like Anomalous Self-Experiences (IPASE). In Study 1, an overinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 89 publications
1
50
0
Order By: Relevance
“…The items are clusterd into five dimensions, representing qualitatively different aspects of self-disorder: 1) Cognition; 2) Self-Awareness and Presence; 3) Consciousness; 4) Somatization and 5) Demarcation/Transitivism. Recently, the scale has been used in studies on psychosis proneness (Cicero et al, 2017) and among schizophrenia spectrum patients (Cicero, Klaunig, Trask, & Neis, 2016). We used a Polish version of the IPASE (Gaweda et al, 2018c).…”
Section: Self-disturbances (Sd)mentioning
confidence: 99%
See 1 more Smart Citation
“…The items are clusterd into five dimensions, representing qualitatively different aspects of self-disorder: 1) Cognition; 2) Self-Awareness and Presence; 3) Consciousness; 4) Somatization and 5) Demarcation/Transitivism. Recently, the scale has been used in studies on psychosis proneness (Cicero et al, 2017) and among schizophrenia spectrum patients (Cicero, Klaunig, Trask, & Neis, 2016). We used a Polish version of the IPASE (Gaweda et al, 2018c).…”
Section: Self-disturbances (Sd)mentioning
confidence: 99%
“…It is a demanding tool and thus not suitable for a screening assessment in large populations. However, since 2017 there is a new tool available for measuring SD in a self‐report manner – The Inventory of Psychotic‐Like Anomalous Self‐Experiences (IPASE) (Cicero, Neis, Klaunig, & Trask, ). A very recent study has confirmed construct validity of the IPASE with correlation coefficients with the EASE reaching about 0.9 (Nelson et al, ), which suggests the IPASE may be a satisfactory proxy or initial assessment of SD.…”
Section: Introductionmentioning
confidence: 99%
“…They were considered potential preclinical experiences preceding impairing psychotic symptoms or psychotic disorders. Finally, a study evaluating measurement tools in the psychotic prodrome described PLE as including ‘magical ideation, perceptual aberration, schizotypal personality disorder, and dissociation’ …”
Section: Resultsmentioning
confidence: 99%
“…Whereas the experimental approach highlights prediction impairments, phenomenological analysis provides testable hypotheses regarding the interaction between retention (retained information) and protention (prediction) mechanisms. 3 Inventory of Psychotic-Like Anomalous Self-Experiences (IPASE), 4 and Self-Experience Lifetime Frequency (SELF) 5 scale has been conducted to identify phenomena associated with each scale. Results: Hundreds of items can be abbreviated to 22 phenomena.…”
Section: Methodsmentioning
confidence: 99%